PEMBERDAYAAN USAHA MIKRO DI MASA PANDEMI COVID-19 MELALUI PENGOLAHAN BUAH KELAPA OLEH PELAKU USAHA PEREMPUAN DI DESA KEMBES 1, KECAMATAN TOMBULU, KABUPATEN MINAHASA - Paskanova Christi Gainau; Yuli Rawun; Peggy Rumenser (Universitas Negeri Medan, 2021)
Covid-19 has reduced the competitiveness of micro businesses. Women as micro-entrepreneurs are also affected by this. In order to support the sustainability of micro businesses in the midst of this crisis, the community service team conducted community service in Kembes 1 Village, Minahasa Regency. The target subjects of this service are women entrepreneurs who are engaged in selling food, cakes and beverages. In this service, business actors are encouraged to innovate the products they sell, one of which is by utilizing the main commodity which is abundant in Kembes Village, namely coconut fruit. Business women are taught to process coconut fruit into durable coconut milk which is sold to residents' homes, food stalls and supermarkets. The coconut processing process is carried out hygienically using a special tool that the team has provided. Business women are trained to identify opportunities in the midst of a crisis and to improvise by utilizing resources (coconuts) as a product that the community tends to need. Based on this community service activity, as a follow-up, business actors need to establish good relationships with customers as a form of building trust and networking. This is important because trust and networking can enable businesses to survive a crisis. In addition, policy makers such as the village government should support the effort to use brand for this product for easily sell in supermarket. Furthermore, assistance and support during times of crisis are very important to support their going concern.